Analysis of the Effectiveness of Marker-Assisted Selection (MAS) in Breeding High-Yielding Plants - Nur Nazhifah Adyputri; Nanda Adrian Mursalim; Sri Mardawiyah; Yusminah Hala (BIOPENDIX, 2026)
Global food security demands more precise and efficient plant breeding strategies to develop high-yielding varieties. Marker-Assisted Selection (MAS) is a molecular approach that utilizes genetic markers such as SSRs, SNPs, and InDels to identify superior genotypes from early growth stages. This study employs a Systematic Literature Review (SLR) method following PRISMA guidelines to analyze the effectiveness of MAS in enhancing crop productivity compared to conventional methods. Review results indicate that MAS can accelerate breeding cycles, improve selection accuracy, and support strategies such as foreground selection, background selection, and gene pyramiding across various commodities, including rice, maize, wheat, soybean, and alfalfa. Significant success is observed in improved disease resistance, abiotic stress tolerance, and yield stability. However, the implementation of MAS still faces challenges, including high operational costs, limited laboratory infrastructure, the complexity of quantitative traits, and the need for marker re-validation across different genetic backgrounds. Future prospects suggest that the integration of MAS with genomic selection, artificial intelligence, and CRISPR-Cas9 technology will strengthen data-driven predictive breeding systems. Consequently, MAS can be viewed as a strategic solution to accelerate the development of high-yielding superior varieties and support the global food security agenda.